2018
DOI: 10.2147/ndt.s165295
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory interactions of resting-state brain functional connectivity in major depressive disorder

Abstract: BackgroundMajor depressive disorder (MDD) is mediated by chronic dysregulation of complex neural circuits, particularly the specific neurotransmitters or other neural substrates. Recently, both increases and decreases in resting-state functional connectivity have been observed in patients with MDD. However, previous research has only assessed the functional connectivity within a specific network or some regions of interests, without considering the modulatory effects of the entire brain regions. To fill in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Decreased VMHC was found in STG, the insula, and the precuneus [28]. In ICA studies, abnormally increased functional connectivity was found between the precuneus/posterior cingulate cortex (PCC) and the left lateral parietal cortex (LPC), and the abnormally decreased coupling was found between the bilateral anterior portion of dlPFC [26,38]. In the seed‐based analysis, the most common region of interest (ROI) is the amygdala.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased VMHC was found in STG, the insula, and the precuneus [28]. In ICA studies, abnormally increased functional connectivity was found between the precuneus/posterior cingulate cortex (PCC) and the left lateral parietal cortex (LPC), and the abnormally decreased coupling was found between the bilateral anterior portion of dlPFC [26,38]. In the seed‐based analysis, the most common region of interest (ROI) is the amygdala.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies reported abnormal functional connectivity in the resting state (Tab 328], and two performed the independent component analysis (ICA) [26,38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another result is decreased connectivity between the right IC and left pTFus C. Insular connectivity changes in MDD give contradictory results (32,33). A study showed a positive correlation between the severity of hopelessness in MDD and right ventral ACC and right insular ReHo (34).…”
Section: Interpretation Of the St + Nhe Group's Post-treatment Rsfc Changesmentioning
confidence: 99%